1986
DOI: 10.1161/01.str.17.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor effects of dimethyl sulfoxide on cat cerebral arteries in vitro and in vivo.

Abstract: SUMMARY We studied the direct vascular effects of dimethyl sulfoxide (DMSO) in isolated middle cerebral arteries and on pial arteriolar caliber after subarachnoid perivascular microinjection in chloralose-anesthetized cats, and on brain retraction in cats given DMSO intravenously. DMSO did not constrict isolated cerebral arteries at any of the concentrations studied (10~'° to 4 x 10~' M). In middle cerebral arteries precontracted with potassium, 5-hydroxytryptamlne, prostagiandin F 2 alflha , or with mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Pitts et al [13] showed that DMSO (>10 mmol/l) inhibited high K + -, 5-hydroxytryptamine-, or prostaglandin F 2α -induced contractions in isolated cat cerebral arteries, and DMSO (>1%) increased the cat pial arteriolar caliber in artificial cerebrospinal fluid. Because a high concentration of DMSO increased the osmolality of the Krebs' solution, the authors concluded that this was the mechanism through which DMSO induced vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Pitts et al [13] showed that DMSO (>10 mmol/l) inhibited high K + -, 5-hydroxytryptamine-, or prostaglandin F 2α -induced contractions in isolated cat cerebral arteries, and DMSO (>1%) increased the cat pial arteriolar caliber in artificial cerebrospinal fluid. Because a high concentration of DMSO increased the osmolality of the Krebs' solution, the authors concluded that this was the mechanism through which DMSO induced vasorelaxation.…”
Section: Discussionmentioning
confidence: 99%
“…DMSO has a wide spectrum of biological activities, including high penetrating activity and significant vasoactive effects on blood vessels [138,139] . It is used for local treatment of trauma, arthrosis, and rheumatoid a r t h r i t i s [ 1 4 0 , 1 4 1 ] .…”
Section: Pharmacological Effects Of Dimethyl Sulfoxide (Dmso)mentioning
confidence: 99%
“…XA was dissolved into saline solution and the pH was adjusted to 7.4 with 1N NaOH. We did not use DMSO to avoid influences on vasocontraction (Pitts et al, 1986). …”
Section: Methodsmentioning
confidence: 99%